The Use of Different Types of Natural Feeds to Enhance Growth and Survival Rates of Freshwater Lobsters (Cherax quadricarinatus) - Muh Azrul Syamsah H Sunani; Indra G Ahmad; Mita Alvionita; Arafik Lamadi (Faculty of Fisheries and Marine, Universitas Riau, 2024)
The freshwater lobster (Cherax quadricarinatus) is a precious commodity within the freshwater aquaculture sector. It is essential to investigate the effects of different natural feeds on lobster growth to enhance aquaculture practices. This study aimed to identify the types of natural feed that influence and improve freshwater lobster juveniles' growth and survival rate. This study was conducted from January to February 2024 at the Kasih Karunia Suwawa Aquaculture Hatchery. A Completely Randomized Design (CRD) was applied, with four treatment groups: Treatment A (bean sprouts), Treatment B (Tubifex sp.), Treatment C (tofu residue), and Treatment D (a combination of bean sprouts, Tubifex sp., and tofu residue). The feed was administered daily at 7% of the total biomass, with a feeding frequency of twice per day. Data were analyzed using ANOVA with SPSS software. The observed parameters included length growth, weight growth, survival rate, and moulting frequency. The results showed that Treatment B (Tubifex sp.) yielded the best growth and moulting frequency, with length growth at 0.76 cm, weight growth at 0.70 g, and moulting frequency at 0.67. The highest survival rate, at 96.67%, was observed in Treatment D (bean sprouts + Tubifex sp. + tofu residue). ANOVA results indicated that different types of natural feeds did not significantly impact the growth and survival of freshwater lobsters.